EXTERNAL COOLING SYSTEM DEVELOPMENT IN RADIOFREQUENCY ABLATION WITH BIPOLAR FORCEPS ELECTRODE - Giantra, Ardityo
Radio frequency ablation has been used in many surgery procedures to disrupt the abnormalities in biological tissue. The procedure results in permanent damage to the tissue. The common problem faced is the uneven distribution of necrotic tissue that led to a limited lesion size. Limited lesion size happen because thermal transfer is stopped in charring tissue. Charring tissue decrease its value in electrical and thermal conductivity at a certain temperature. There should be method to overcome the needs to produce more even and larger lesion size. This study proposed an improvement to the procedure with experiment and modeling methods. Exterior cooling system is built as an addition instrument to the radio frequency ablation instruments available. The study was done to quantify the cooling effect of the external cooling system used. Object of the study is part of liver tissue in ex-vivo condition. Cooling coil is supplied with cooled water at constant temperature and set into several volume flow rates through peristaltic pump. The coil contacted to the surface of the tissue when ablation was executed. The ablation was done for a minute with bipolar forceps electrode at 30 W output setting. Temperature measurement of the tissue were observed during ablation time. The ablated tissues were cut, the width and the height of the lesion were measured for analysis. The modeling is done through COMSOL Multiphysics software. The with-cooling coil experiment showed the maximum temperature reached was lower than the no-cooling coil experiment. The experiment also showed that by using exterior cooling coil there were increases in the size of the lesions. Models acquired from the software show the similar temperature profile and lesion size with the experiment. The use of external cooling system as additional instrument is suitable as an addition instruments to be used in electrosurgery which objectives is to make a larger lesion size.